Induksi Kalus Nepenthes mirabilis(Lour.) Druce Menggunakan NAA danTDZ - Nina Nurussakinah; Murni Dwiati; Iman Budisantoso (Fakultas Biologi Universitas Jenderal Soedirman, 2022)
Nepenthes sp. has a characteristic in the form of a modified leaf tip into a pitcher. Nepenthes mirabilis (Lour.) Druce in its original habitat is widely hunted for sale. Propagation of N. mirabilis in nature has very little success rate, to overcome this it is necessary to propagate it by means of in vitro culture and use young leaf explants to form callus. Growth regulators such as Auxins (NAA) and Cytokinins (TDZ) can stimulate callus growth. Auxins can stimulate callus formation by stimulating cell expansion and cytokinins can stimulate the cell division process. The purpose of this study was to determine the effect of NAA and TDZ in inducing N. mirabilis callus and to determine the interaction between NAA and TDZ in inducing N. mirabilis callus. The experimental design used was a factorial CRD pattern, with two factors, namely NAA and TDZ. NAA consists of four levels, namely, 0 mg / L (N0); 0.5 mg / L (N1), 1 mg / L (N2) and 1.5 mg / L (N3). TDZ also consists of four levels, namely 0 mg / L (T0); 1 mg / L (T1); 2 mg / L (T2) and 3 mg / L (T3). Each treatment was repeated three times. The results showed that the addition of NAA and TDZ had an effect on callus induction of N. mirabilis. The TDZ concentration of 1 mg / L (T1) stimulated callus induction, especially the percentage of callus formation and callus diameter. Meanwhile, NAA 1 mg / L (N2) boosted the percentage of N. mirabilis callus formation.